Pemberdayaan Petani Melalui Pengembangan Melon Lokal Madura sebagai Upaya Peningkatan Pendapatan Kelompok Tani Padimas-Pamekasan - Ahmad Syaiful Umam; Arifah Husna; Maria Ulfa; Dian Krisna Firnanda; Royhanatul Jannah; Dian Fedita Sari; Reyhana Azarela Olgarista (Jurnal Pelayanan Masyarakat, 2025)
Farmer empowerment through the development of local agricultural commodities is an important strategy to increase farmers’ income and strengthen the independence of farmer groups. This community service activity aimed to enhance the capacity of the Padimas Farmer Group in Sana Tengah Village, Pasean Sub-district, Pamekasan Regency, through the development of local Madura melon as a regional flagship commodity. The program was implemented using a participatory–collaborative approach that actively involved farmers in all stages of the activity, including the identification of local needs and potentials, provision of demonstration plot land, cultivation assistance, and continuous monitoring and evaluation. The melon demonstration plot served as a practical learning medium for farmers in applying cultivation techniques adapted to local agroclimatic conditions. The results showed that the development of the local melon demonstration plot significantly improved farmers’ knowledge and skills in melon cultivation, with a plant survival rate reaching 99%. In addition, this activity supported the establishment of a group-based flagship commodity with promising economic value and market opportunities. Overall, the farmer empowerment program contributed positively to strengthening farmers’ economic independence and has the potential to serve as a model for sustainable horticultural agribusiness development in the Pamekasan region.